Dynamic Changes in DNA Methylation Occur during the First Year of Life in Preterm Infants - Piyasena, Chinthika; Cartier, Jessy; Provençal, Nadine; Wiechmann, Tobias; Khulan, Batbayar; Sunderesan, Raju; Menon, Gopi; Seckl, Jonathan R.; Reynolds, Rebecca M.; Binder, Elisabeth B.; Drake, Amanda J. (Frontiers in Endocrinology, 2016)
Background: Preterm birth associates with a substantially increased risk of later cardiovascular disease and neurodevelopmental disorders. Understanding underlying mechanisms will facilitate the development of screening and intervention strategies to reduce disease risk. Changes in DNA methylation have been proposed as one mechanism linking the early environment with later disease risk. We tested the hypothesis that preterm birth associates with altered DNA methylation in genes encoding insulin-like growth factor 2 (IGF2) and FK506 binding protein 5 (FKBP5), which appear particularly vulnerable to early life adversity. Methods: 50 preterm infants were seen and assessed at birth, term equivalent age, 3 months and 1 year corrected ages; 40 term infants were seen at birth, 3 months and 1 year. Saliva was collected for DNA extraction at birth, term and 1 year. Pyrosequencing of bisulfite converted DNA was performed to measure DNA methylation at specific CpG sites within the IGF2 and FKBP5 loci. Results: Weight and head circumference was reduced in preterm infants at all time points. Preterm infants had a higher percentage body fat at term corrected age but this difference was not persistent. DNA methylation at the differentially methylated region (DMR) of IGF2 (IGF2DMR2) and FKBP5 was lower in preterm infants at birth/term corrected age compared to term infants at birth. IGF2DMR2 and FKBP5 methylation was related to birthweight standard deviation score in preterm infants. Amongst preterm infants, social deprivation was an independent contributor towards reducing DNA methylation at IGF2DMR2 at birth and term corrected age and maternal smoking was associated with reduced DNA methylation at FKBP5 at birth. There were no persistent differences in DNA methylation at 1 year of age. Conclusions: Changes in DNA methylation were identified at key regions of IGF2/H19 and FKBP5 in preterm infants in early life. Potential contributing factors include maternal smoking and social deprivation. However, these changes did not persist at one year of age and further longitudinal studies are required to determine any associations between altered DNA methylation in the perinatal period of individuals born preterm and their long-term health.